2021
DOI: 10.3390/nu13113702
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Short-Chain Fatty Acids in Mediating Very Low-Calorie Ketogenic Diet-Infant Gut Microbiota Relationships and Its Therapeutic Potential in Obesity

Abstract: As the very low-calorie ketogenic diet (VLCKD) gains increased interest as a therapeutic approach for many diseases, little is known about its therapeutic use in childhood obesity. Indeed, the role of VLCKD during pregnancy and lactation in influencing short chain fatty acid (SCFA)-producing bacteria and the potential mechanisms involved in the protective effects on obesity are still unclear. Infants are characterized by a diverse gut microbiota composition with higher abundance of SCFA-producing bacteria. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 194 publications
(256 reference statements)
1
29
0
Order By: Relevance
“…The ketogenic diet is characterized by maintaining a carbohydrate intake below 50grams a day or by being no more than 10% of total energy ingested. Previously, this diet was related to the treatment of epilepsy and as a method of losing weight, and is still used, presenting good results [ 22 , 23 ]. Now it has reappeared with a role closer to the sport field due to the interest generated by aerobic athletes in obtaining a vast energy source.…”
Section: Introductionmentioning
confidence: 99%
“…The ketogenic diet is characterized by maintaining a carbohydrate intake below 50grams a day or by being no more than 10% of total energy ingested. Previously, this diet was related to the treatment of epilepsy and as a method of losing weight, and is still used, presenting good results [ 22 , 23 ]. Now it has reappeared with a role closer to the sport field due to the interest generated by aerobic athletes in obtaining a vast energy source.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a total of 16 studies were selected, including 11 RCTs and 5 observational studies. The study selection process is shown in Figure 1 [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The present study is a systematic review of the literature on randomized clinical trials, observational studies, and systematic reviews. It was carried out following the criteria defined in the PRISMA declaration for the preparation and the development of systematic reviews and meta-analyses [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The KD was also shown to be effective and well-tolerated in infants with intractable epilepsy [ 4 ]. A very low-calorie KD was used as a therapeutic approach for many diseases, such as epilepsy or obesity [ 3 , 5 , 6 ]. There are different types of the KD and the classic KD used for therapeutic diet in drug resistant epilepsy consists of a main proportion of fat, which is commonly a 4:1 ratio, and for children, a 3:1 ratio of fat to carbohydrate, plus protein [ 7 ].…”
Section: Introductionmentioning
confidence: 99%